Currículo: a implantação do laptop educacional no município de Cordeirópolis – SP - Talarico, Felipe Fernando (2019)
This research is part of the research line New Technologies in Education of the Graduate Program in Education: Curriculum of the Pontifical Catholic University of São Paulo. It aims to investigate the pedagogical practice of teachers in the first year of implementation of the project to introduce educational laptops in a school in Cordeirópolis, state of São Paulo. With a qualitative approach, five teachers from the 1st to the 5th grade of elementary school were observed in a school, as well as interviews with the coordination of the project analyzed and a questionnaire applied to teachers about the perception of the use of technologies in their practice. As main results, it was identified that teachers make systematic use of technologies in both planning and daily life, which contributes to the process of integration of technologies in their practice and curriculum. Favorable infrastructure conditions and management also contributed to the process